№ 1. 1) 8у - 3(2у - 3) = 7у - 2(5у + 8), 2) 5(2у - 9) + 6у = 4(3у - 2) - 21,
8y - 6y + 9 = 7y - 10y - 16, 10у - 45 + 6у = 12у - 8 - 21,
2y + 9 =-3у - 16, 16у - 45 = 12у - 29,
2у + 3у = -16 - 9, 16у - 12у = -29 + 45,
5y = -25, 4у = 16,
у = -25 : 5, у = 16 : 4,
y = -5; у = 4;
№ 2. 1) 5(3 - 2у) - 4(9 - у) = 3(у + 5),
15 - 10y - 36 + 4y = 3y + 15,
-6y - 21 = 3у + 15,
-6у - 3у = 15 + 21,
-9y = 36,
у = 36 : (-9),
y = -4;
2) 14(2х - 3) - 5(х + 4) = 2(3х + 5) + 5х,
28x - 42 - 5x - 20 = 6x + 10 + 5x,
23х - 62 = 11х + 10,
23x - 11x = 10 + 62,
12x = 72,
х = 72 : 12,
x = 6;
3) 9(3х - 7) + 3(8х - 11) = 3(9х + 8),
27x - 63 + 24x - 33 = 27x + 24,
51x - 96 = 27х + 24,
51х - 27х = 24 + 96,
24x = 120,
х = 120 : 24,
x = 5;
4) 6(7х - 11) - 13(х - 6) = 14(2х + 1),
42x - 66 - 13x + 78 = 28x + 14,
29x + 12 = 28х + 14,
29x - 28 х = 14 - 12,
х = 2;
№ 3. 1) 1,2х + 7 = 2x + 3, (здесь, видимо, пропущен х)
1,2x - 2х = 3 - 7,
-0,8x = -4,
х = -4 : (-0,8),
x = 5;
2) 8,3 - 2,1х = 2(1,5х + 11,8),
8,3 - 2,1х = 3х + 23,6,
-2,1х - 3х = 23,6 - 8,3,
-5,1х = 15,3,
х = 15,3 : (-5,1),
х = -3;
3) 9(13 - 0,8х) + 6,7 = 7,1х - 5,
117 - 7,2х + 6,7 = 7,1х - 5,
-7,2х + 123,7 = 7,1х - 5,
-7,2х - 7,1х = -5 - 123,7,
-14,3х = -128,7,
х = -128,7 : (-14,3),
х = 9.
Пошаговое объяснение:
1) 4 ( 3 - х ) - 11 = 7 ( 2х - 5 )
12х-3х-11=14х-35
9х-14х=11-35
-5х= -24
х=24\5 =4,8 ответ:4,8
3) - 7у = -21
у=-21\7 у=-3 ответ:-3
4) 48у = -16
у=-16\48 у=- 1\3 ответ:-1\3
5) 5у +9 = 0
5у=-9
у=-9\5 ответ:-9\5
6) 5у + 4 = у - 12
5у-у=-12-4
4у=-16
у=-16\4 у=-4 ответ:-4
7) 45 - ( 6 - у ) = 14
45-6+у=14
39-14+у=0
25+у=0
у=-25 ответ:-25
8) 420 - 6у = 240
420-240-6у=0
180-6у=0
-6у=-180
у=-180\-6 у=30 ответ:30
9) 15 - 3у = -6
-3у=-6-15
-3у=-21 у=-21\-3 у=7 ответ:7
10) 70 + ( 60 - у ) = 130
70+60-у=130
130-у=130
-у=130-130 у=0
11) 7 ( 3х - 1) = 5( х - 3 )
21х-7=5х-15
21х-5х=-15+7
16х=-8 х=-1\2
12) 2/7у + 3/7 = 1/7у |7
2у-3=у
2у-у=3
у=3
0,25×4,02=
4,75×3,05=
8,125×5,25=
6,4×2,6=